MANAJEMEN STRATEGI DALAM PENGEMBANGAN BUDAYA AKADEMIK MADRASAH MUALLIMIN - Ari Prayoga; Irawan Irawan (Program Studi Pendidikan Agama Islam Fakultas Agama Islam Universitas Islam Darul 'Ulum Lamongan, 2020)
Academic culture that has not been implemented in accordance with the vision, mission and objectives of the madrasa includes students who are not present in the learning process because they play truant at class time, educators who also hold positions outside the madrasah as religious counselors, educators at the tsanawiyah madrasa levels, educators are not every day in school and only comes when they have class time, centralized administration in administration that doubles as an educator. This study aims to uncover the managerial strategies of madrasas in developing academic culture in accordance with the vision and mission of the institution. The method of research using descriptive qualitative intends to uncover the phenomena that occur in the muallimin madrasa. Data collection techniques with the study of interviews with the madrasa head, madrasa deputy head of the curriculum and educators, documentation studies relating to the academic culture of madrasas and madrasa environment observation. The results showed that; first, the vision and mission are formulated in accordance with national foundation and education guidelines; second, the strategic plan is divided into three namely short, medium and long; third, self-development includes three types, namely counseling, extracurricular and habituation; fourth, the foundation of organizational culture compilation namely socio-culture, juridical and Islamic; fifth, operational arrangements based on Islam, nationalism and culture.